Biodiversity of Plants and Birds in Reclamation Area of PT Bukit Asam, Muara Enim, South Sumatera - Dimaz Danang Al-Reza; Lilik Budi Prasetyo; Rahmad Hermawan (Jurnal Manajemen Hutan Tropika, 2016)
Mining activities will reduce species diversity, whereas forest reclamation would restore the species diversity, which was previously a forested area. This research was conducted in PT Bukit Asam area, in 6 locations, and in natural forest, as a comparison. The objective of this research was identifying biodiversity of plants and birds in a reclamation area which had different planting years through an approach of diversity indices of vegetation and birds (H'), index of species similarity of plants and birds, and leaf area index (LAI). Research results showed that secondary succession occurred in the reclamation area. The value of plant diversity index in reclamation area of 1995 planting year exhibited diversity values which approached that of natural forest, except for undergrowth vegetation. Index of plant species similarity between reclamation area and natural forest did not show any presence of similar communities, but the reclamation area of 1995 planting year exhibited values of plant species similarity indices at all strata, ranging from undergrowth vegetation, seedlings, saplings, poles, and trees. Index of bird diversity in reclamation area of planting the year 1998 possessed the highest value and approached that of natural forest, namely 2.43. Reclamation area of 1998 planting year possessed the highest similarity index of bird species, namely 50%. Reclamation area of the planting year 1995 possessed LAI which approached natural forest, namely 1.89.  The older the planting year, the larger was the value of LAI, except for the disturbed reclamation area, namely reclamation area of 1996 planting year and reclamation area of 2001 planting year.